(untitled) (Texas Journal of Engineering and Technology, 2022)
The existing system has the ability to yet lack the ability to control indoor humidity. Green House Monitoring and Controlling is a complete system designed to monitor and control the humidity inside a green house. This software uses an Android mobile phone, connected using Wifi to a central server which connects via serial communication to a microcontroller and humidity sensor. The result shows that thecondition specified in sensor’s datasheet and system in reality is appropriate. The achieved test result concludes that the system is working properly